صعوبات التعلم و التعليم في ظل جائحة كورونا - لمام ثريا (كلية العلوم الإجتماعية, 2022)
ملخص الدراسة: يقال أن الحاجة أم الختراع، هذه المثل الذي جسد لنا حالة دول العالم ومن بينها الجزائر كيف آل بها المآل حين فاجأها الفيروس الخطير كوفيد- 91 ، والذي أثر على مختلف الميادين والمجالات خاصة المجال التعليمي، حيث تم اللجوء إلى التعليم عن بعد تحت ظروف الحجر الصحي، فيأتي هذا البحث المعنون بصعوبات التعلم والتعليم عن بعد في ظل جائحة كورونا للتعرف على مدى تأثير هذا الوباء، والتطرق لجوهر التعلم والتعليم عن بعد بما فيه من إيجابيات و سلبيات، و الأهم التعرف على الصعوبات التي واحهها الطلبة تحت الظروف الصحية المستعصية الكلمات المفتاحية : الفيروس الخطير كوفيد- 91- المجال التعليمي- ظروف الحجر الصحي- الظروف الصحية- الطلبة . Study summary: It is said that necessity is the mother of invention, this proverb that embodied for us the situation of the countries of the world, including Algeria, how the money came to it when the dangerous virus “Covid-91” surprised it, which affected various fields and fields, especially the educational field, where distance education was resorted to under quarantine conditions. This research, entitled Difficulties of learning and distance education in light of the Corona pandemic, comes to know the extent of the impact of this epidemic, and to address the essence of distance learning and education, including its pros and cons, and most importantly, to identify the difficulties faced by students under difficult health conditions. key words : The dangerous virus Covid-91 - the educational field - quarantine conditions - health conditions - students.
دراسة ميدانية على عينة من طلبة جامعة عبد الحميد بن باديس
Keywords: الفيروس الخطير كوفيد- 91- المجال التعليمي- ظروف الحجر الصحي- الظروف الصحية- الطلبة .